Implementation support for contingency management: preferences of opioid treatment program leaders and staff - Scott, Kelli (Implement Sci Commun, 2021)
BACKGROUND: Contingency management (CM), a behavioral intervention that provides incentives for achieving treatment goals, is an evidence-based adjunct to medication to treat opioid use disorder. Unfortunately, many front-line treatment providers do not utilize CM, likely due to contextual barriers that limit effective training and ongoing support for evidence-based practices. This study applied user-informed approaches to adapt a multi-level implementation strategy called the Science to Service Laboratory (SSL) to support CM implementation. METHODS: Leaders and treatment providers working in community-based opioid treatment programs (OTPs; N = 43) completed qualitative interviews inquiring about their preferences for training and support implementation strategies (didactic training, performance feedback, and external facilitation). Our team coded interviews using a reflexive team approach to identify common a priori and emergent themes. RESULTS: Leaders and providers expressed a preference for brief training that included case examples and research data, along with experiential learning strategies. They reported a desire for performance feedback from internal supervisors, patients, and clinical experts. Providers and leaders had mixed feelings about audio-recording sessions but were open to the use of rating sheets to evaluate CM performance. Finally, participants desired both on-call and regularly scheduled external facilitation to support their continued use of CM. CONCLUSIONS: This study provides an exemplar of a user-informed approach to adapt the SSL implementation support strategies for CM scale-up in community OTPs. Study findings highlight the need for user-informed approaches to training, performance feedback, and facilitation to support sustained CM use in this setting.